Influence of macroporosity on NIH/3T3 adhesion, proliferation, and osteogenic differentiation of MC3T3-E1 over bio-functionalized highly porous titanium implant material - Alves, A. C.; Thibeaux, R.; Toptan, F.; Pinto, A. M.P.; Ponthiaux, P.; David, B. (Wiley, 2018)
Highly porous Ti implant materials are being used in order to overcome the stress shielding effect on orthopedic implants. However, the lack of bioactivity on Ti surfaces is still a major concern regarding the osseointegration process. It is known that the rapid recruitment of osteoblasts in bone defects is an essential prerequisite for efficient bone repair. Conventionally, osteoblast recruitment to bone defects and subsequent bone repair has been achieved using growth factors. Thus, in this study highly porous Ti samples were processed by powder metallurgy using space holder technique followed by the bio-functionalization through microarc oxidation using a Ca- and P-rich electrolyte. The biological response in terms of early cell response, namely, adhesion, spreading, viability, and proliferation of the novel biofunctionalized highly porous Ti was carried out with NIH/3T3 fibroblasts and MC3T3-E1 preosteoblasts in terms of viability, adhesion, proliferation, and alkaline phosphatase activity. Results showed that bio-functionalization did not affect the cell viability. However, bio-functionalized highly porous Ti (22% porosity) enhanced the cell proliferation and activity.
Keywords: Bio-functionalization; Microarc oxidation; Osseointegration; Porous Ti